Educational Anamnesis and Emotional Well-being in Lifelong Learning for Older Adults: Strategies and Assessments for Comprehensive Care - Rosser Limiñana, Pablo; Soler Ortiz, Seila (Biomedical. Journal of Scientific & Technical Research, 2024)
This proposal for incorporating the methodology of anamnesis into the educational field, specifically aimed at the education of older adults, anticipates the implementation of a comprehensive approach that encompasses both emotional well-being and effective learning for this group. The goal is to personalize teaching and optimize the social and psychological well-being of students by adapting strategies from the medical field to pedagogy. This, in turn, aims to provide useful information to professionals in comprehensive care for older adults.
Keywords: well-being; emotions; older adults; lifelong learning; statistical analysis; educational anamnesis